2020
DOI: 10.1002/htj.21894
|View full text |Cite
|
Sign up to set email alerts
|

MHD nonlinear natural convection flow of a micropolar nanofluid past a nonisothermal rotating disk

Abstract: The aim of this analysis is to examine the steady, laminar boundary layer flow of a micropolar nanofluid owing to a rotating disk in the presence of a magnetic field and thermal and solutal nonlinear convection and nonisothermal parameters. The governing joined partial differential equations are converted into nonlinear ordinary differential equations by means of available transformations. The equations are calculated using the method bvp4c from Matlab software. The convergence test has been maintained; for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Wubshet and Shanker [11] have informed the manipulates of magnetic area and thermal radiation on nanofluid past non-isothermal ball along extending layer by non-isothermal wall temperature in addition to non-isothermal thermal fluctuation. Recently, Wubshet and Chaluma ([12], [13], [14]) have been investigated that increasing in thermal nonlinear convection exhibits the enhancing feature on Nusselt number, skin friction coefficient, velocity fields close the outside of sphere, disk and cylinder while it shows the decreasing behaviour on thermal field. This effect happen due to higher density of the fluid which relates to lower the momentum diffusion and higher thermal diffusion close wall of sphere, disk with cylinder All the above quoted papers have been presenting the current past a flat surface, isothermal sphere,disk, cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Wubshet and Shanker [11] have informed the manipulates of magnetic area and thermal radiation on nanofluid past non-isothermal ball along extending layer by non-isothermal wall temperature in addition to non-isothermal thermal fluctuation. Recently, Wubshet and Chaluma ([12], [13], [14]) have been investigated that increasing in thermal nonlinear convection exhibits the enhancing feature on Nusselt number, skin friction coefficient, velocity fields close the outside of sphere, disk and cylinder while it shows the decreasing behaviour on thermal field. This effect happen due to higher density of the fluid which relates to lower the momentum diffusion and higher thermal diffusion close wall of sphere, disk with cylinder All the above quoted papers have been presenting the current past a flat surface, isothermal sphere,disk, cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Significance of viscous dissipation on stagnancy flow of Oldroyd-B liquid due to a Riga plate was numerically deliberated by Nayak et al 27 They confirmed the relaxation-retardation plays prominent role in escalating the thermal fields. Ibrahim and Zemedu 28 used bvp4c MatLab code to inspect the impression of magnetic field on the flow of micropolar nanoliquid triggered by a revolving disk. A similar kind of study with flow of micropolar liquid over a cylindrical pipe was carried out by Yadav and Verma, 29 they computed the simultaneous solutions for two distinct fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on the movement mechanism of non-Newtonian liquids over diverse geometries can be perceived in ref. 2325…”
Section: Introductionmentioning
confidence: 99%